ANALYSIS OF IMPLEMENTATION OF SERVICE TO TAX MANDATORY IN PRATAMA TAX SERVICE OFFICE - Bandiyono, Agus; Rama Daneshwara (Dinasti Publisher, 2019)
This research aims to analyze the implementation of the service STO Jakarta Kelapa Gading according to the Circular of the Director-General of Tax No. SE - 84 / PJ / 2011 and SE - 09 / PJ / 2013, and within six components of the assessment Pilot KPP. The research method used to obtain and analyze data that can support this writing is a qualitative method through interviews and document collection through library research. The implementation of excellent service is an obligation of the KPP as a public service provider. To carry out performance evaluations and give awards to offices that have performed excellent service according to existing regulations, an assessment was held to obtain a pilot KPP title held by the Ministry of Finance Assessment Team. This assessment is regulated in Decree of the Minister of Finance of the Republic of Indonesia Number 128 / KMK.01 / 2013 concerning Guidelines for Evaluation of Pilot Service Offices in the Ministry of Finance and Decree of the Director-General of Tax Number KEP-161 / PJ / 2015 concerning Guidelines for Evaluation of Pilot Services Offices at Regional Office Level Directorate General of Taxes. Jakarta Kelapa Gading KPP is the first KPP Pilot Model in the North Jakarta area. Therefore following the implementation of existing services so that the KPP can get a pilot KPP title.